Syariah Governance Pada Perbankan Syariah - Joko Hadi Purnomo (Universitas Islam Lamongan, 2016)
Shariah governance is concatenation of two concepts, these are the concept of good corporate governance and shariah compliance. The governance of banks applies the principle of transparency, accountability, responsibility, professionalism and fairness whereas shariah compliance is the duty of Islamic bank to meet compliance with Islamic principles. The operation of Islamic banks must strictly adhere to the provisions of shariah. The application of shariah governance is the implementation of good corporate governance principles and shariah compliance. The implementation of shariah governance in Islamic banks relies on surveillance covering all research activities, observation and measurement on the course of operations, both internally and externally. Based on the above background, author makes formulations of the problem; (a) how is the implementation of Shariah governance in Islamic bank?; (b) How is the supervision of the application of Shariah governance in Islamic bank?. The purpose of this paper is to know the implementation of Shariah governance in Islamic banks and to know the supervision of the implementation of Shari'a governance in Islamic bank. The implementation of GCG in Islamic banking creates transparency to prevent fraud, conduct accountability with the system that controls the relationship between the organs of company, do responsibility, keep independence, and keep in touch with fairness. The application of sharia compliance at Islamic banks without riba in bank transactions, no vagueness (gharar) in bank transactions, there is no gambling (maisir) in bank transactions. Bank conducts business on the basis of allowed (halal) profits. Banks manage zakat, sadaqah, and infaq according to the shariah provisions. The implementation of sharia governance in Islamic banks relies on surveillance covering all research activities, observation and measurement on the course of the operation by using elements of the AGM, Board of Commissioner, Board of Auditor, Shariah Supervisory Board (DPS), Director of Compliance, Internal Audit, Internal Shari'a Reviewers of SKAI and external monitoring system consists of elements of the Financial Services Authority (OJK), Public Accountant, National Sharia Council (DSN) and Stakeholders.Keywords: Corporate, syariah, Governance